Variabilidade Isoenzimatica em Populações Naturais de Drosophila maculifrons e Drosophila ornatifrons (Diptera: Drosophilidae) em Fragmentos De Mata Atlântica no Sul e Sudeste do Brasil - Silva, Daniele Cortes da (2011)
The guarani group of Drosophlila have wide distribution to the Neotropical region. The Drosophila maculifrons species (subgroup guaramunu) and Drosophila ornatifrons (subgroup guarani), are typical forest species, which ecological and genetic aspects are virtually unknown. The fragmentation of native areas strongly influence ecological and evolutionary processes, and constitute the most serious threat to biological diversity. Some studies have pointed out that the species of the guarani group is an important bioindicator of the conservation state in different environments. Thus studies on the genetic variability of natural populations are extremely important to understand evolutionary processes that act in maintainance of biodiversity. The objective of this study was to estimate the genetic variability through isoenzyme variation, in two species of the guarani group, Drosophila maculifrons and Drosophila ornatifrons in four fragments of Atlantic forest geographically isolated, two in Southeast (São Paulo) and two in South (Paraná) of Brazil. For D. maculifrons, the results indicated a high genetic differentiation among populations. The values of distance and genetic identities Nei (1972) and the Neighbor-Joining and UPGMA cluster analyse indicated that there was no correlation between genetic distance and geographic positioning. A high deficiency of heterozygotes was also observed, possibly due to factors such as Wahlund effects and selection against heterozygotes. The populations of D. ornatifrons showed a moderate genetic differentiation and a certain association between genetic differentiation and geographic positioning. These results reflects the evolutionary history of these species and consequences of habitat fragmentation that may influence the processes of adaptation to environmental heterogeneity, gene flow among populations and the effects of genetic drift. Thus new research with different markers, and studies on the basic biology of these species are extremely important to better understand the processes responsible for the maintenance of genetic variability found.